If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -9p = 0 Solving 10 + -9p = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -9p = 0 + -10 Combine like terms: 10 + -10 = 0 0 + -9p = 0 + -10 -9p = 0 + -10 Combine like terms: 0 + -10 = -10 -9p = -10 Divide each side by '-9'. p = 1.111111111 Simplifying p = 1.111111111
| (6x-5)(x^2-8x+1)= | | 2235.75=2200(1+0.25r) | | 2n/5n | | 15x^2-14x-49= | | 16an-19an+8b+9an+12b= | | (X)(x-2)(x-6)=96 | | 8a+12a-7b-9b-11b= | | -3y+9=0 | | logx^2-logx+20=0 | | 7y-(10y-9x)= | | -5b-5=0 | | Lnx^2-Lnx+20=0 | | (x-7)+x+(2x-14)=67 | | 45t-5t^20=0 | | (x+3)(x^2+2x-15)=0 | | (x-7)*x*(2x-14)=67 | | -7*k=0 | | 20=45t-5t^2 | | 3X-12X=4 | | y=4*2-2 | | x+(2x+18)+(x-12)+(x+4)=2.5 | | y=4*0-2 | | 2x+7=-25 | | 18x=72 | | 17=(n-1)(n-2)(n-3)(n-4)-2n^3 | | 0.5x+0.75-2=4x-2+6 | | 2=0.3x | | 3x-12=10-x | | 7b+7=0 | | -5x(x+1)=13 | | 2a-3.5=3 | | 9*0+2y=-72 |